PAINTED TERRAPIN (Batagur borneoensis) PREFERENCE ON NESTING SITE IN SERUWAY DISTRICT, ACEH TAMIANG - Hana Shafira Aulia; Mufti Sudibyo; Lazuardi Lazuardi (JBIO: jurnal biosains (the journal of biosciences), 2021)
Painted terrapin (Batagur borneoensis) is a critically endangered freshwater turtle that has an annual migration behavior from freshwater rivers to the coast during the breeding season. In the habitat selection, painted terrapin also have a tendency that is influenced by certain factors to meet their needs. This underlies the possible of environmental characteristics influence on their nesting site selection and the eggs production. This study aims to determine the correlation between eggs amount that obtained from each nest with : 1) distance of nesting site from vegetation, 2) distance between each nests, 3) distance nesting site from coastline, and 4) the slope of nesting site. Data collected by observation in the field and using Purposive sampling method to determine 4 research stations. Data was analyzed with multiple linear regression analysis by using IBM SPSS 22. The results showed the types of vegetation around the nesting sites were Casuarina sp., Ipomoea pes-caprae, Cyperus sp., Scaevola taccada, Thespesia populnea and Avicennia sp. The result showed the average of distance between nesting site is  90.7±124.4 meters, the average distance of nesting site to vegetation about 2.5 ± 3.8 meters, the average distance of nest to the coastline is  4.6±2.7 meters, the average slope of the nesting sites about 10.7°±3.1°, and the average number of eggs is 16.9±3.1 eggs. Based on multiple linear regression analysis, the eggs amount is not influenced by the distance of nesting site from coastline, the distance to each nesting site, the distance of nesting site with vegetation and the slope of nesting site.